THE LATE STAGE OF EVOLUTION OF THE NORTHERN PART OF THE OKHOTSK-CHUKCHI VOLCANOGENIC BELT - Belyi V.F.; Raikevich M.I.; Belaya B.V. (My University, 1997)
As a result of field studies conducted in the Enmyvaam River basin in 1991 and 1993, it has been found that stratigraphic units of volcanic rocks of the late stage of the Okhotsk-Chukchi volcanogenic belt (OCVB) evolution make up a succession (from the base upward) of the Ergyvaam, Emuneret, and Enmyvaam formations. The work also resulted in obtaining new palynologic and magnetostratigraphic data. Rocks with reversed magnetization (the middle part of the Emuneret Formation) were revealed and observed for the first time among volcanic complexes of the OCVB. The rocks occur stratigraphically above layers with the Ust'-Emuneret floral assemblage referred by palynological data to the late Turonian. The reversed polarity zone (R-zone) revealed correlates with the Klyuev R-zone (the middle Coniacian) of the general paleomagnetic scale for the Phanerozoic of continents. The lower part of the Enmyvaam Formation comprises the late Turonian-early Senonian palynological assemblage. Taking into account the stratigraphic position of the Enmyvaam Formation and the normal magnetization of its rocks, the formation is dated back to the Santonian. This was the first attempt to apply the combined paleophytological, palynological, and magnetostratigraphic data for correlation the Cretaceous volcanogenic deposits in northeastern Russia.
Keywords: Cretaceous; Santonian; Coniacian; Turonian; Мезозой::Меловая::Верхний::Туронский; Mesozoic::Cretaceous::Upper::Coniacian; Мезозой::Меловая::Верхний::Коньякский; Mesozoic::Cretaceous; Mesozoic::Cretaceous::Upper::Santonian; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая; Мезозой::Меловая::Верхний::Сантонский